Laser tube bending process for stainless steel 304 - Imhan, Khalil Ibraheem (2017)
The invention of the laser light in the mid-last-century has opened a wide spectrum of laser material processing due to being unique, coherent and monochromatic. Moreover, the laser forming process of materials has a potential feature to produce new shapes of sheets or tubes that cannot be achieved through conventional methods. In this study, the focus is placed on the laser tube bending process because of its importance in large-term applications. Molds and dies are not currently in use; thus, no external forces that can cause tube bending defects such as wrinkling, wall thinning, springback and cross-section distortion. In addition, the process is flexible and can be controlled by laser parameters, either individually or in combination with other processes. An analytical model is used to study the effect of the average laser power, angular scanning speed, laser beam diameter, and specimen geometry during the laser tube bending process. The material specification impacts on the process behavior are analytically investigated for different material such as Copper, Aluminum, Nickel and Stainless Steel 304. To verify the analytical results, a high-power pulsed Neodymiumdoped Yttrium Aluminium Garnet (Nd-YAG) laser of the maximum laser power of 300 (W) emitted at 1064 nm with a fibre-coupled head is used to irradiate stainless steel 304 tubes with a 12.7 mm diameter, 0.6 mm thickness. A motorized rotational stage with computerized control is used to hold and rotate the specimen tube 180° for one semi-circle scanning, with a maximum angular scanning speed of 40 deg/sec. The deflection of the tube directly was measured to determine the bending angle, which it was 1.33 degrees when the average laser power is 200 W and the angular scanning speed is 30 deg/sec. The study also discovered that the laser softening heat treatment on the tube specimens can enhance the material absorption of the laser light and the mechanical formability; hence, the bending angle produced is increased by 70%. The experimental results become higher than the analytical results as the average laser power exceeds 100 W in both cases, with and without the laser softening heat treatment. Thus, due to the rise of the specimen’s temperature, hence, the analytical model is modified and developed to involve the changes of material specifications by adding a factor to the model once the laser power becomes more than 100 W. This behavior may be due to the temperature rise of the tube material from the heat generated by the laser. The modified model has been tested and optimized by using particle swarm optimization (PSO) to find the perfect specifications of the material affecting the laser tube bending process such as thermal expansion coefficient, specific heat, yield stress, and absorption coefficient. The analytical and experimental results are in the same trend but with different slopes; the bending angle determined is directly proportional to the average laser power, and inversely proportional to the angular scanning speed. Meanwhile, increasing the tube diameter and thickness reduces the value of the bending angle produced. In addition, the material specifications of the bent tube have significant effects on the process, especially the expansion coefficient which is directly proportional to the bending angle and the density as well as the specific heat which are inversely proportional with the bending angle.